CORRELATING THE CURVE DISTANCE BETWEEN THE DISTAL of THE CANINES TO THE COMBINED WIDTH of THE SIX ANTERIOR TEETH WHEN SELECTING DENTURE TEETH FOR DIFFERENT ETHNIC GROUPS - Varjao, Fabiana M.; Nogueira, Sergio Sualdini [UNESP] (Mosby-elsevier, 2012)
Statement of problem. To select the width of denture teeth, the distance between the marks indicating the location of the canines is usually measured around the curvature of the wax occlusal rim; however, most manufacturers' mold charts provide the measurements of the artificial 6 anterior teeth as if they were on a straight line.Purpose. The purpose of this study was to investigate whether the curve distance between the distal surfaces of the maxillary canines can be related to the combined width (straight measurement) of the 6 anterior teeth in 4 ethnic groups.Material and methods. Maxillary stone casts were obtained for 160 dentate subjects of 4 ethnic groups (40 whites, 40 blacks, 40 multiracial - descendants of white and black parents, and 40 Asians). The width of each maxillary anterior tooth was measured on the casts with sliding calipers. The combined width of the 6 anterior teeth (CW) corresponded to the sum of the width of each anterior tooth. The curve distance between the distal surfaces of the canines (CD) was measured by using dental tape and sliding calipers. The Pearson correlation coefficient and regression analysis were used to evaluate the relationship between CD and CW in each ethnic group (alpha=.05).Results. The mean CD and CW values (in mm) obtained were: whites (CD=52.12; CW=45.65); blacks (CD=56.10; CW=48.13); multiracial (CD=53.58; CW=46.54); and Asians (CD=53.29; CW=46.60). Significant (P<.001) correlations between CD and CW measurements were observed for all ethnic groups studied (whites, r=0.957; blacks, r=0.803; multiracial, r=0.917; and Asians, r=0.881). The following linear regression equations were obtained: whites [CD=1.1(CW)+0.3]; blacks [CD=0.95(CW)+9.3]; multiracial [CD=1.2(CW)-1.1]; and Asians [CD=1.0(CW)+5].Conclusions. The curve distance between the distal surfaces of the maxillary canines can be accurately related to the combined width of the 6 anterior teeth in the selection of denture teeth for the studied ethnic groups. (J Prosthet Dent 2012;107:400-404)